Avoiding the Agreement Trap: Teams Facilitate Impasse in Negotiations with Negative Bargaining Zones. (November 2014) - Cohen, Taya R.; Leonardelli, Geoffrey J.; Thompson, Leigh
Abstract The agreement trap occurs when negotiators reach deals that are inferior to their best alternative agreements. This article extends prior negotiation research by investigating whether teams display greater wisdom than solos in knowing when to walk away from the negotiating table and thereby avoid the agreement trap. Two experiments compared teams and solos in a negotiation in which reaching agreement was unwise because of misaligned interests. The negotiation involved a real estate transaction in which the optimal solution was for the parties to declare an impasse. Study 1 found that two‐ and three‐person teams were significantly more likely than solos to impasse. Study 2 found that the party faced with the greater need to make accurate judgments about the alignment between their own and their counterpart's interests benefited most from the addition of a teammate. These findings offer insight into why the agreement trap occurs and how it can be reduced.